2019
DOI: 10.5222/mmj.2019.53503
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in a Case of Auditory Neuropathy Spectrum Disorder with CAPOS Syndrome

Abstract: Auditory neuropathy spectrum disorder (ANSD) is a hearing disorder which characterized with normal outer hair cell function but disrupted neural synchrony in the afferent auditory pathway. CAPOS (cerebellar ataxia, areflexia, pes cavus, optic atrophy, and sensorineural hearing loss) syndrome can manifest itself with ANSD and this rare situation and audiological rehabilitation outcomes have not well documented in the literature. We aim to present a cochlear implant user subject with CAPOS syndrome and ANSD. A 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…CAPOS syndrome (Cerebellar ataxia, Areflexia, Pes cavus, Optic atrophy, and Sensorineural hearing loss) with acquired hearing impairment as a prominent feature 44 , is a rare neurological disorder associated with mutation in the ATP1A3 gene. Han et al 45 and Atilgan et al 46 described the remarkable benefits of cochlear implantation, assuming synaptophysin as the hearing loss pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CAPOS syndrome (Cerebellar ataxia, Areflexia, Pes cavus, Optic atrophy, and Sensorineural hearing loss) with acquired hearing impairment as a prominent feature 44 , is a rare neurological disorder associated with mutation in the ATP1A3 gene. Han et al 45 and Atilgan et al 46 described the remarkable benefits of cochlear implantation, assuming synaptophysin as the hearing loss pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…CAPOS syndrome (Cerebellar ataxia, Areflexia, Pes cavus, Optic atrophy, and Sensorineural hearing loss) with acquired hearing impairment as a prominent feature 44 , is a rare neurological disorder associated with mutation in the ATP1A3 gene. Han et al 45 and Atilgan et al 46 described the remarkable benefits of cochlear implantation, assuming synaptophysin as the hearing loss pathogenesis. Brown Vialetto Syndrome is a neurodegenerative disorder characterised by hearing loss and ponto-bulbar palsy due to mutations in the genes encoding the riboflavin transporters, and vitamin supplements can thus be useful.…”
Section: Geneticsmentioning
confidence: 99%
“…Tranebjaerg et al (Fang et al, 2019) stated that four CAPOS patients received CI, two of whom gained significant benefits and the other two was relatively poor. In contrast, Atilgan et al (2019) documented a much more beneficial effect of CI in a patient with CAPOS syndrome as compared to patients with SNHL. These findings could be explained by the fact that the ATP1A3 gene is expressed not only in synapse but also in postsynaptic spiral ganglion cells (SGNs).…”
Section: Discussionmentioning
confidence: 90%
“…In fact, in most postsynaptic AN, CI has a dubious outcome (Supplementary Table 2). An example is CI in the SGNs (Fasquelle et al, 2011;Eppsteiner et al, 2012;Atilgan et al, 2019). CI performed earlier in TMPRSS3 generated a preferable outcome, while the outcomes in later implantees were not as favorable (Chung et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The CAMP has been utilized in a wide variety of settings by different research groups, including pediatric, hybrid CI, Australian, Turkish and Korean populations. 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 Notably, it has also been shown to have clinical feasibility in a large multicenter study involving 14 institutions and has been reported twice in longitudinal follow-up of patients after cochlear implantation. 43 , 44 , 45 …”
Section: Overview Of Current Available Music Assessment Toolsmentioning
confidence: 99%